Minimally invasive repair technique for pectus excavatum deformity: The Marmara experience [Pektus ekskavatum deformitesinde minimal i̇nvaziv onarım tekniǧi: Marmara deneyimi] - (:unkn) unknown (Marmara University, 2011)
Objective: Minimally invasive repair of pectus excavatum (MIRPE) have gained support recently as it can be applied in both children and adults successfully. Our objective was to review minimally invasive repair of pectus excavatum in Marmara University School of Medicine. Patients and Methods: One hundred and sixty eight cases who had minimally invasive repair between August-2005 and November-2010 were reviewed retrospectively. Cases were evaluated according to demographics, surgical indication, form of deformity, concommitant anomalies, family history, previous corrections, number of bars, duration of the operation, concommitant procedures, pain management, peri-andpostoperative complications, bar removal, and patient satisfaction. Results: One hundred and forty one cases were male, 27 were female. Median age was 16. The deformity was symmetric in 110, asymmetric in 58 cases. The most common concommitant anomaly was scoliosis in 27 cases. 26 cases had a family history for deformity. 14 cases had a previous open repair. 1 bar in 105, 2 in 58, 3 in 5 cases were placed for correction. The median duration of the operation was 60 minutes. The most common perioperative complication was pneumothorax in 12 cases. The most common postoperative complication was wound infection in 8 cases. Bar removal was performed in 7 cases with only one recurrence. Quality-of-life questionnaires revealed that 94% of patients were satisfied with the treatment. Conclusion: This minimally invasive technique is a promising procedure for better cosmetic results and high levels of patient satisfaction.
Keywords: Chest wall deformity; Minimally invasive surgery; MIRPE; Nuss procedure; Pectus excavatum